2012
DOI: 10.1097/pai.0b013e31821ba035
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Determination of ETS-1 Oncoprotein Expression in Urothelial Carcinomas of the Urinary Bladder

Abstract: ETS-1 protooncogene is an important transcription factor that plays a role in the regulation of physiological processes, such as cell proliferation and differentiation. ETS-1 is thought to be related to the growth of carcinoma cells by its regulation of the transcription of matrix metalloproteinases and urokinase-type plasminogen activator. In this study, we aimed to investigate the expression pattern of ETS-1 oncoprotein in urothelial carcinomas of the urinary bladder and determine its relationship with histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…It should be noted that the results of the correlation of ETS-1 expression with the malignant phenotype of bladder cancer in our study is contrary to the findings from Aysegul S, et al They reported that most of the low-grade and noninvasive bladder cancer largely expressed ETS-1, and that high-grade and invasive bladder cancer showed a frequent decrease or loss of ETS-1expression [ 19 ]. But they only used immunohistochemical staining to investigate the expression of ETS-1 and did not perform the functional experiments in their studies.…”
Section: Discussioncontrasting
confidence: 99%
“…It should be noted that the results of the correlation of ETS-1 expression with the malignant phenotype of bladder cancer in our study is contrary to the findings from Aysegul S, et al They reported that most of the low-grade and noninvasive bladder cancer largely expressed ETS-1, and that high-grade and invasive bladder cancer showed a frequent decrease or loss of ETS-1expression [ 19 ]. But they only used immunohistochemical staining to investigate the expression of ETS-1 and did not perform the functional experiments in their studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Ets1 is an oncogene whose expression is frequently upregulated in a variety of human tumors of different tissue origins (for example, [115120]). Using transgenic mouse models, where we are able to inducibly over-express Ets1 in stratified squamous epithelial cells, we have demonstrated that Ets1 induces a number of pro-oncogenic changes when it is expressed in epithelial cells including a block to terminal differentiation accompanied by high secretion of matrix metalloproteases (Mmps), epidermal growth factor ligands, and inflammatory mediators [121, 122].…”
Section: Ets1 In Hematopoietic Tumorsmentioning
confidence: 99%
“…ETS1 encodes a member of the ETS family of transcription factor which is involved in stem cell development, cell senescence and death, and tumorigenesis. Sari, Aysegul et al found that non-muscle-invasive tumors had significantly higher ETS1 expression than that of the muscle-invasive tumors [ 40 ], indicating its special role in superficial bladder carcinoma. Additionally, the promoter of telomerase reverse transcriptase ( TERT) gene frequently mutated in bladder carcinoma in which ETS1 bond to the altered promoter and promoted bladder carcinoma migration and progression [ 41 ].…”
Section: Discussionmentioning
confidence: 99%